2019
DOI: 10.1542/peds.2019-3147
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Provider Workforce

Abstract: This technical report reviews education, training, competency requirements, and scopes of practice of the different neonatal care providers who work to meet the special needs of neonatal patients and their families in the NICU. Additionally, this report examines the current workforce issues of NICU providers, offers suggestions for establishing and monitoring quality and safety of care, and suggests potential solutions to the NICU provider workforce shortages now and in the future. To meet the critical and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 45 publications
0
33
0
2
Order By: Relevance
“…Other challenges included determination of the best content for both neonatal PA fellows and new graduate NNPs. Since the model of training NNPs has been suggested as appropriate for training neonatal PAs,1,2 and because the role responsibilities are similar, the content and competencies that are the basis of NNP education are used for the neonatal PAs. This is in contrast to the content provided when neonatal PA fellows attend neonatologist fellowship educational offerings, as in other neonatal PA fellowship programs 3,4.…”
Section: Discussionmentioning
confidence: 99%
“…Other challenges included determination of the best content for both neonatal PA fellows and new graduate NNPs. Since the model of training NNPs has been suggested as appropriate for training neonatal PAs,1,2 and because the role responsibilities are similar, the content and competencies that are the basis of NNP education are used for the neonatal PAs. This is in contrast to the content provided when neonatal PA fellows attend neonatologist fellowship educational offerings, as in other neonatal PA fellowship programs 3,4.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the American Academy of Pediatrics Committee on Fetus and Newborn have identified that neonatologists will increasingly need to collaborate with a variety of professionals, including APRNs and PAs, to meet the needs of the NICU population 7,28. Also, they recognized the training model for NNPs as well developed and how it may serve as a model for other NICU care providers 7,28.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-five percent of these respondents planned to increase the use of neonatal PAs in the future 6. The use of both NNPs and PAs as neonatal APPs has been supported by members of the American Academy of Pediatrics 7…”
mentioning
confidence: 99%
“…[12][13][14] Many of the pediatric subspecialties have also raised concerns about workforce shortages. [15][16][17][18][19][20][21] With the recognition that pediatric physician-scientists have been the cornerstone for advances in genomics, precision medicine and biomedical research, the decline in the physician-scientist workforce adds further vulnerability. Physician scientists represent only 1.5% of the workforce and organizational strategies have been developed to improve the pipeline of adult and pediatric physician scientists.…”
Section: Introductionmentioning
confidence: 99%